New photocyclization of 2-(tert-butoxycarbonyl) amino-3,3-dichloroacrylonitrile - Melnychuk, P.V.; Shablykin, O.V.; Shablykina, O.V. (Reports of the National Academy of Sciences of Ukraine, 2022)
For the first time, a 2-(allylamino)-3, 3-dichloroacrylonitrile derivative was used in a photoinitiated intramolecular [2+2] cycloaddition, which led to the formation of N-Boc-protected 5, 5-dichloro-2-azabicyclo[2. 1. 1]- hexane-1-carbonitrile — a unique 2-azabicyclo[2. 1. 1]hexane derivative with nitrile group and dichloromethylene moiety. Intramolecular [2+2] photocyclization of 2-(allylamino)acrylates is the foremost way to build 2, 4-methanoprolines, that are still a small group conformationally rigid analogue of Proline derivatives. But this reaction has not been studied for the corresponding acrylonitriles. The capable substrate for [2+2] photocyclization — tert-butyl allyl(2, 2-dichloro-1-cyanovinyl)carbamate — was synthesized by us in high yield from available reagents. Simple synthetic techniques was using: one pot conversion tert-butyl (2, 2, 2-trichloro-1-hydroxyethyl) carbamate to tert-butyl (2, 2-dichloro-1-cyanovinyl)carbamate with subsequent N-allylation. Intramolecular [2+2] cycloaddition was carried out in acetonitrile solution by irradiation with the light of 368 nm wavelength; the use of xanthone instead of the standard photosensitizer acetophenone can reduce the time of target product formation from 12 to 6 hours. The successful using of substituted 2-amino-3, 3-dichloroacrylonitrile in photochemical isomerization make it possible to consider these compounds as promising substrates for the synthesis of bridged bicyclic amines.